Suvarnadvipa : Ancient Indian Colonies in the Far East. Volume 2: Cultural History - Majumdar, R.C. (Brill | Manohar Publishers & Distributors, 2024)
South East Asian history is one of the most unique histories, as it was marked by the influences of Indic, Chinese, and local cultures. Suvarnadvipa is a two-volume series, which covers the political and cultural history of South East Asian history. This volume deals with the cultural history of South East Asia during ancient times. The author discusses literature, religion, art, and society in greater detail, which was prevalent during ancient times. Works of literature composed in Java, Bali, and the Malay Peninsula are covered in this volume, as it was written in Sanskrit, Old Javanese, and others. It also covers the history of Buddhism (mainly the Mahayana sect) and Hinduism, along with their religious texts, before the coming of Islam. The chapters on the history of art and architecture are covered comprehensively. It talks about the religious and non-religious structures, the influence of Hindu and Buddhist arts, sculpture art, and different art forms practiced in Bali, Sumatra, Borneo, Philippines, and Tapanauli region. This book is essential for scholars and researchers interested in the pre-Islamic history of South East Asia.